CHARACTERISTICS OF NATIONALISM AND UNIVERSALISM IN HISTORICAL FILMS OF THE PERIOD OF INDEPENDENCE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article discusses the features of nationalism and universality in historical films, paying attention to their themes, acting, and directing.